Effects of cellulose nanofiber on the thermal, mechanical, and optical properties of triacetate cellulose nanocomposites - C. M. Wu; K. S. Danh; A. N. Nakagaito (eXPRESS Polymer Letters)
In this study, well-dispersed nanocomposite films with triacetate cellulose (TAC) as a matrix and reinforced with lemon peel-cellulose nanofibers (lemon peel-CNF) were developed. The nanofibers in aqueous solution were solvent-exchanged to methanol by a series of centrifuging and re-dispersing steps. Afterward, using the solution casting method, the mixture of recycled TAC (rTAC) film and nanofibers prepared by stirring combined with ball milling technique to achieve full dispersed solution was coated onto glass to obtain a thin film. The dispersion effect of CNF in TAC was observed by transmission electron microscopy. The optical, mechanical, and thermal properties of the nanocomposite films were characterized experimentally. The results showed that with varying CNF content (1–7 wt%), the haze was slightly increased while the transmittance was not affected compared with that of rTAC film (92.7%). The addition of CNF increased the tensile strength by 60%, tensile strain by 150%, and yield strength by 50%. Creep compliance improved for all nanocomposites compared with rTAC film. CNF led to a significant reduction in the thermal expansion properties of rTAC film.